Micro-modelling and analysis of actual and idealised cancellous structure - Abdul Kadir, Mohammed Rafiq; Syahrom, A.; Yusof, M. A. R.; Kamsah, N. (Springer Berlin Heidelberg, 2008)
Cancellous bone has a complex structure consisting of plates and struts with the density varies depending on the anatomical site. In this study, three idealized architecture were developed based on morphological indices of cancellous bone: the hexagonal, the prismatic and the quadratic crystal shape (QCS). The three architectures were then developed into two types of microstructure, the first consists of struts only and the second consists of a combination of plates and struts. The microstructures were transformed into finite element models and uniaxial compression was applied to all six idealized cancellous models as well as on the actual cancellous bone specimen obtained from microCT. Contour plots of von Mises stress and displacement were then analysed. Results showed that all models with a combination of plates and struts have higher rigidity compared to the one with struts only. Between the three architectures, the hexagonal was the stiffest among the plates and struts microstructure whilst the prismatic was the most flexible. For the struts microstructure, the hexagonal was found to be the most flexible whilst the prismatic the most stiff. The hexagonal architecture with plates and struts showed similar resemblance to the actual cancellous bone.